2015
DOI: 10.5812/rijm.3(2)2015.27082
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity of Antibodies Against Hepatitis A Virus in Mashhad, Northeast of Iran: A Cross-Sectional Community-Based Study During 2009

Abstract: Background: Hepatitis A Virus (HAV) is the most common cause of acute viral hepatitis worldwide, mostly in developing countries.Objectives: This population-based survey was performed to investigate HAV seroprevalence in Mashhad, northeast of Iran. Patients and Methods: A cross-sectional study was performed on 1563 randomly selected individuals from general population of Mashhad, Iran, between May to September 2009. Serum samples were tested for total anti-HAV antibody using an enzyme-linked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…HAV seroprevalence was 86.76% in 17-year-old adolescents in the Golestan province (13), 61.6% in individuals under 20 who were referred to a hospital in Tehran (14), 79.3% in 15 to 20-year-old persons referred for pre-marriage consultations in the Fars province (9), 64.7% in 15 to 24-year-old adolescents in Mashhad in the Razavi Khorasan province (15), and 79.4% in 16 to 29-year-olds in Shiraz, the provincial city of the Fars province (8). In contrast, HAV seroprevalence was 38.9% in under 25-year-olds in Sari (center of Mazanderan province) (16), 10% in 6-20-year-olds in a population- based study in Isfahan province (17), and 3.9% in children under 15 in Kashan (in the Isfahan province) (18), which are much lower than in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…HAV seroprevalence was 86.76% in 17-year-old adolescents in the Golestan province (13), 61.6% in individuals under 20 who were referred to a hospital in Tehran (14), 79.3% in 15 to 20-year-old persons referred for pre-marriage consultations in the Fars province (9), 64.7% in 15 to 24-year-old adolescents in Mashhad in the Razavi Khorasan province (15), and 79.4% in 16 to 29-year-olds in Shiraz, the provincial city of the Fars province (8). In contrast, HAV seroprevalence was 38.9% in under 25-year-olds in Sari (center of Mazanderan province) (16), 10% in 6-20-year-olds in a population- based study in Isfahan province (17), and 3.9% in children under 15 in Kashan (in the Isfahan province) (18), which are much lower than in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several diseases, such as HBV, HCV, and HIV, are also considered to be transmitted through tattooing; this is primarily due to sharing needles and other equipment and poor disinfecting. Our patient had a history of tattooing about two months before admission [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, anti-HBc is a positive marker in patients. This condition includes anti-HBc IgM dominant class during the window period in acute hepatitis, in cases of ended acute infection and undetected serum level of anti-HBs, and long-term chronic HBV infection with undetected HBsAg level [ 2 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperendemic pattern was reported by earlier published investigations in different provinces of Iran. A high prevalence rate of HAV infection was reported in some cities and provinces of Iran, such as 80.65% in Ahwaz (23), 79.2% in Hamedan (24), 85% in Tehran, 96% in Hormozgan, 99% in Golestan (13), 94.9% in Qazvin (25), 70% in Mashhad (26), 82% in Sari (27), 88.6% in Zabol (28), 90.8% in Shahrekord (15), and 89.5% in Yazd (29); however, HAV seroprevalence in Fars (66.2%), Esfahan (67.5%), Kermanshah (50.6%), and Zanjan (58.09%) provinces, Iran, demonstrated a lower rate of infection (24,30). Ghorbani et al reported that immunity status against HAV among Iranian military draftees in Tehran was 97.63% in 2007 (31).…”
Section: Discussionmentioning
confidence: 99%